How close does the apple fall to the tree? Some evidence on intergenerational occupational mobility from India - Sripad Motiram; Ashish Singh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Using data from the India Human Development Survey (IHDS) 2005, we examine intergenerational occupational mobility in India, an issue on which very few systematic and rigorous studies exist. We group individuals into classes and document patterns of mobility at the rural, urban and all-India levels, and for different caste groups. We find substantial intergenerational persistence, particularly in the case of low-skilled and low-paying occupations, e.g. almost half the children of agricultural labourers end up becoming agricultural labourers. We also document differences across caste groups. Overall, our results suggest considerable inequality of opportunity in India.
Keywords: D31; D63; 330; intergenerational mobility : inequality of opportunity; distributive justice; social class; Arbeitsmobilität; Intergenerationale Übertragung; Erwerbsverlauf; Indien